2003
DOI: 10.1111/j.1365-2621.2003.tb05800.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved Culturing Techniques for Campylobacter

Abstract: Improved techniques for culturing and enumerating Campylobacter jejuni were developed. Parameters included (1) growth vessel type, (2) growth atmosphere, (3) incubation time, and (4) frequency of subculturing. Improved growth and consistent morphology were obtained using a tissue culture flask compared with an Erlenmeyer flask or a test tube as well as exposure to modified atmosphere (10% CO 2 , 85% N 2 , and 5% O 2 ). When cultures of C. jejuni were incubated more than 24 h, transformation to the coccoid incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…The initial source in human infections is largely caused by direct or indirect contamination from faecal or intestinal material of food animals. The main initial source of contamination is poultry products (Hirsh, 1999a;Koenig, 2005), the infection occurring after food has been improperly cooked or contaminated (or re-contaminated) after any cooking stage (Koenig, 2005;Reilly & Gilliland, 2003). However, some occurrences are associated with raw milk (Hirsh, 1999b;Reilly & Gilliland, 2003) and contaminated water supplies (Hirsh, 1999b;Koenig, 2005;Reilly & Gilliland, 2003).…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…The initial source in human infections is largely caused by direct or indirect contamination from faecal or intestinal material of food animals. The main initial source of contamination is poultry products (Hirsh, 1999a;Koenig, 2005), the infection occurring after food has been improperly cooked or contaminated (or re-contaminated) after any cooking stage (Koenig, 2005;Reilly & Gilliland, 2003). However, some occurrences are associated with raw milk (Hirsh, 1999b;Reilly & Gilliland, 2003) and contaminated water supplies (Hirsh, 1999b;Koenig, 2005;Reilly & Gilliland, 2003).…”
Section: Introductionmentioning
confidence: 95%
“…Although any person can be affected (Beumer, de Vries, & Rombouts, 1992;Roberts et al, 1998), the symptoms are normally more serious in children, elderly people and persons with underlying health problems (Roberts et al, 1998;(www.health.vic.gov.av, 2000)) Campylobacter spp. is part of the intestinal flora of several animals (Carter et al, 1995;Reilly & Gilliland, 2003;Tortora et al, 2002). The initial source in human infections is largely caused by direct or indirect contamination from faecal or intestinal material of food animals.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…A comparison of three gas generating systems (GRJ, CGP and plastic bags used as plate container and filled with premixed microaerobic gas) for growing C. jejuni on agar plates, revealed that while these three methods provided no significant differences for culturable cells, the size of the colonies on plates using GRJ were significantly smaller than those obtained from the two other methods (Haines et al, 2011). It was also mentioned that the helical shape of the cells was maintained in vented tissue culture flasks incubated under microaerobic atmosphere (Reilly and Gilliland, 2003).…”
Section: Effect Of Media and Gas On Campylobacter Growthmentioning
confidence: 96%